A pilot study for the application of World Class Manufacturing techniques in the fibre-cement industry - Aggenbach, Eduard Johannes Wiese (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Eng. (Industrial)) -- University of Stellenbosch, 1991.